A Survey on H∞ Control-Based Output Feedback Techniques - Pandiya, Govind Prasad; Vidyarthi, Abhay (Engineering, Technology & Applied Science Research, 2023)
The study of 2-D discrete systems has always been a preferred choice amongst researchers and academics, due to its diversified applications in most practical applications. For more than two decades, research based on H∞ control techniques has been the focus of attention, as it plays a key role in the design and development of various applications based on signal processing and control theory. In many practical applications, the accessibility of the state vectors is not possible, and, in such cases, output feedback techniques are most appropriate. This paper presents a detailed survey based on H∞ control-based output feedback techniques for discrete 2-D systems.